Kritik Komunikasi Kampanye Publik pada Kampanye Stunting Dinas Kesehatan Kulon Progo Tahun 2018 - Ahmad Syafi'i Lubis (Jurnal Media dan Komunikasi Indonesia, 2022)
Nowadays the issue of children, food and nutrition because cases of malnutrition are still high. Indonesia is still a country with children with "malnutrition status" which is below the standard of World Health Organization it is below 10%. The problem of malnutrition affects the development of children or is known as stunting. There are 10 villages in Kulon Progo which have become the stunting special location. Kulon Progo is the first area in DIY to conduct a stunting campaign against the public. This study aims to analyze and criticize more deeply the strategies and tactics in public communication carried out by Dinas Kesehatan Kulon Progo to communicate stunting campaigns, using a qualitative descriptive approach. This study uses the concept of Atkin & Rice, Ostegard, Lee, and Rogers & Storey about Public Campaign Communications and also Public Campaign concept from Lee & Ostegard. Data collection methods and techniques used are secondary data of literature reviews, thesis, journal articles, and other sources related to the object and research of the researcher. The analytical technique used interactive analysis from Miles & Huberman. Overall, the stunting campaign program still has problems in the planning stage, especially the evaluation of the campaign program which only focuses on the final impact, without evaluating the concept of campaign communication strategies and tactics to be able to identify deficiencies as a reference in developing further strategies and tactics.